The Influence of Human Resource Quality, Information Technology Utilization, and Work Environment on Employee Performance at the Education Office of Mojokerto Regency - Alfiyah Rahmadani; Moh. Heru Budi Santoso (International Publisher, 2025)
This study investigated the influence of human resource quality, the utilization of information technology, and the work environment on employee performance at the Education Office of Mojokerto Regency. A quantitative research design was employed, targeting the entire employee population through a saturated sampling technique, resulting in 83 respondents. Data were collected using structured questionnaires and analyzed through multiple linear regression. The findings revealed that human resource quality, information technology utilization, and the work environment collectively had a significant and positive affect on employee performance. Partially, human resource quality and information technology utilization showed a significant effect, while the work environment variable did not demonstrate a statistically significant impact on performance.